2018
DOI: 10.1111/nep.12968
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal catheter fixation combined with straight upward tunnel and low implant position to prevent catheter malfunction

Abstract: Catheter fixation combined with straight upward tunnel and low implant position can effectively prevent catheter malfunction in PD catheter placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The interventions introduced in the included studies were as follows: catheter type/configuration in 17 studies (36%) 14 30 with the most frequently studied intervention was comparing straight versus coiled intra-abdominal part of the catheters (9 RCTs). Insertion technique in 15 studies (32%) 31 45 with the most frequently studied intervention open versus laparoscopic catheter insertion (4 RCTs), two interventions in 3 studies (6%), 46 –48 and there were 6 other different interventions in 12 studies (26%) (Supplementary Table 1). Study characteristics of the included trials can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interventions introduced in the included studies were as follows: catheter type/configuration in 17 studies (36%) 14 30 with the most frequently studied intervention was comparing straight versus coiled intra-abdominal part of the catheters (9 RCTs). Insertion technique in 15 studies (32%) 31 45 with the most frequently studied intervention open versus laparoscopic catheter insertion (4 RCTs), two interventions in 3 studies (6%), 46 –48 and there were 6 other different interventions in 12 studies (26%) (Supplementary Table 1). Study characteristics of the included trials can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In our review, other outcomes have also been reported frequently like postoperative pain, 35,37,42,43,45,52,53 length of wound, 35,37,45 and incidence of delayed wound healing. 44,49 Postoperative pain is patient-centered and may warrant further characterization in terms of incidence and may be considered as targets for future ISPD PD access guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Experiences in Australia and other countries make it clear that nephrologists can perform these procedures safely and effectively. [16][17][18][19][20] Interventional nephrology is in its infancy in Australia and New Zealand, but may grow as more junior doctors are exposed to it during their training and with the support of the local society. 21 Patients outside of major cities may be the greatest beneficiaries of growth in interventional nephrology given their more limited access to vascular surgeons (demonstrated in the present survey) and their lower rates of commencing dialysis with a functioning fistula.…”
Section: Discussionmentioning
confidence: 99%